Rotational Grazing: A Path to Sustainable Rangeland Management - Hassan, Sawsan; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2024)
Presentation highlighted the significant advantages of rotational grazing as a sustainable practice for managing rangelands. The presentation discussed the challenges associated with continuous grazing, including soil degradation, poor livestock health, and reduced forage productivity. It outlined the benefits of rotational grazing, such as improved soil health, enhanced forage production, and better economic efficiency for farmers. Key points emphasized the importance of grazing behavior, stocking density, and the need for adequate recovery time for forage plants. The presentation concluded that rotational grazing not only boosted productivity and forage quality but also fostered environmental sustainability and economic viability for livestock producers.